A practical approach to special education administration creating positive outcomes for students with different abilities - Earley, James B.; McArdle, Robert J. (Corwin, 2023)
"The goal of the authors is to share what they have learned as veteran special education administrators to assist those in the job or looking to move into the job. The comprehensiveness and complexities of the position can be and are at times overwhelming. Throughout their careers the authors made mistakes, and this book with its short chapters and conversational tone provides insight into decision-making and relationship-building. Included are tips like face-to-face interactions and classroom visitations are essential in assisting staff, students, and building principals; and topics such as the importance of parents in the process, the significance of confidentiality, due process, program development, and working with advocates. This book is a critical tool in the special education administrator's box, and provides practical and friendly advice for a difficult job"--